Fabrication of steel matrix composites locally reinforced with different ratios of TiC/TiB2 particulates using SHS reactions of Ni–Ti–B4C and Ni–Ti–B4C–C systems during casting - Yang, Ya-feng; Wang, Hui-yuan; Liang, Yun-hong; Zhao, Ru-yi; Jiang, Qi-chuan (Materials science & engineering. A, Structural materials : properties, microstructure and processing, 2007)
Steel matrix composites locally reinforced with different molar ratios of in situ TiC/TiB2 particulates (2:1, 1:1 and 1:2, respectively) have been fabricated successfully utilizing the self-propagating high-temperature synthesis (SHS) reactions of Ni-Ti-B4C and Ni-Ti-B4C-C systems during casting. Differential thermal analysis (DTA) and X-ray diffraction (XRD) results reveal that the exothermic reactions of the Ni-Ti-B4C and Ni-Ti-B4C-C systems proceed in such a way that Ni initially reacts with B4C and Ti to form Ni2B and Ti2Ni compounds, respectively, with heat evolution at 1037 deg C; Subsequently, the external heat and the evolved heat from these exothermic reactions promote the reactions forming TiC and TiB2 at 1133 deg C. In the composites reinforced with 1:2 molar ratio of TiC/TiB2, almost all TiB2 grains have clubbed structures, while TiC grains exhibit near-spherical morphologies. Furthermore, TiB2 grain sizes decrease, with the increase of TiC content. In particular, in the composites reinforced with 2:1 molar ratio of TiC/TiB2, it is difficult to find the clubbed TiB2 grains. Macro-pores and blowholes are absent in the local reinforcing region of the composites reinforced with 1:1 and 1:2 molar ratios of TiC/TiB2, while a few macro-pores can be observed in the composite reinforced with 2:1 molar ratio of TiC/TiB2. Moreover, the densities of the composites reinforced with 1:1 and 1:2 molar ratios of TiC/TiB2 are higher than that of the composite reinforced with 2:1 molar ratio of TiC/TiB2. The composite reinforced with 1:2 molar ratio of TiC/TiB2 has the highest hardness and the best wear resistance.